ANALISIS BRAND IMAGE YOGYAKARTA SEBAGAI KOTA PELAJAR - Sigit Haryono (Jurnal Ilmu Komunikasi, 2009)
Yogyakarta as a student city is an asset. Branding activity are maintain this positioning that must be done through marketing strategy. This study is used to support that activity. Brand image Yogyakarta as student city is importance to be done as part of marketing communication to identify the audiences. The aim of the study is are describe attributes of student city and how brand image Yogyakarta as a student city. Research sites are UPN, UGM, and UII students. Samples size are 300 respondents. Questionare used to data collection technique. Data analysis use descriptive statistic with “diagram of snake”. Conclusion of brand analysis show that student city attributes are students from all Indonesia, popular universities, qualified universities, completly collection stores book, low cost stores book, sport facilities, entertainment facilities, residence facilities, reachable living cost. Based on that attributes can be conclusioned that brand image Yogyakarta as a student city are good.